Strategi Pemerintah Dalam Pengembangan Agropolitan Ngebel Di Kabupaten Ponorogo - Bayu Pratama (Jurnal Administrasi Publik, 2016)
Abstract: Strategy of Government in Developing Ngebel Agropolitant in Ponorogo Research is conducted to describe how the Development of Agropolitant Ngebel in Ponorogo. There is some stageholder including farmer in Ngebel Agropolitan, Bapeda Ponorogo , Dinas Pertanian Ponorogo, Dinas Indakop. Kabupaten Ponorogo and Dinas PU Bidang Cipta Karya Kabupaten Ponorogo.Descriptive approach is used in this research with Qualitative research design. Research Objects are: strategy of government in developing Ngebel Agropolitant that consist of human resources development, infrastructure development and agribusiness development, also Supporting and resisting factors.The result of this research showed that development of Ngebel agropolitantÂ  is done by doing the strategy of human resources development through training and socialization, Infarastructure development by finishing indirect infrastructure of agropolitant development, and wide spreading the prime product. such as; durian cultivation, dairy goat cultivation, and fishery cultivation in agribusiness development. Supporting factors are important roles among Stageholders, natural resources such durian commodity, integrated to Telaga Ngebel Tourism, and major-society as a farmer. Resisting factors in this development of Ngebel Agroplitant are Stageholders understating in low-level institution, Agropolitan program is not arranged well yet, there is no irrigation technic. Keywords: Strategy, Agropolitant Area Development Abstrak: Strategi Pemerintah Dalam Pengembangan Agropolitan Ngebel di Kabupaten Ponorogo. Penelitian ini dilakukan untuk mendeskripsikan bagaimana Pengembangan Agropolitan Ngebel di Kabupaten Ponorogo. Ada beberapa Stageholder yang terlibat meliputi petani di Kawasan Agropolitan Ngebel, Bapedda Kabupaten Ponorogo, Dinas Pertanian Kabupaten Ponorogo, Dinas Indakop. Kabupaten Ponorogo dan Dinas PU Bidang Cipta Karya Kabupaten Ponorogo. Penelitian merupakan jenis penelitian diskriptif dengan pendekatan kualitatif. Fokus penelitian ini terdiri dari : strategi pemertintah dalam mengembangkan Agropolitan Ngebel yang meliputi pengembangan sumber daya manusia, pengembangan infrastruktur dan pengembangan agribisinis, serta Faktor pendukung dan penghambatnya. Hasil dari penelitian ini menunjukan bahwa pengembangan Agropolitan Ngebel dilakukan melalui strategi pengembangan sumber daya manusia melalui pelatihan dan penyuluhan, pengembangan infrastruktur melalui pembangunan infrastruktur penunjang pengembangan agropolitan dan pengembangan agribisnis dengan mengembangkan produk unggulan seperti budidaya durian, budidaya kambing Peranakan Etawa, dan budidaya perikanan. Faktor pendukung dalam pengembangan Agropolitan Ngebel adalah peran antar Stageholder (pemangku kepentingan), sumber daya alam berupa komoditas durian, terintegrasi dengan Wisata Telaga Ngebel dan mayoritas penduduk berprofesi sebagai petani. Sedangkan faktor penghambat dalam pengembangan Agropolitan Ngebel adalah pemahaman para Stageholder di tingkat institusi rendah, kegiatan pengembangan agropoitan belum tertata dengan baik, dan tidak ada pengairan teknis. Kata Kunci : Strategi, Pengembangan Kawasan Agropolitan